The Relationship Between Conflict Resolution Approaches and Trust—A Cross Cultural Study - Sullivan, Jeremiah J.; Peterson, Richard B.; Kameda, Naoki; Shimada, Justin Y. (Academy of Management Journal, 1981)
This study investigated whether the manner in which conflicts are resolved in Japanese-American joint ventures in Japan influences the level of future mutual trust. Japanese managers perceived a higher level of future trust when disputes are resolved through conferral, except when an American is in charge of operations. Then they designated contracts requiring binding arbitration.